Conjunctival inclusion cysts following small incision cataract surgery - Narayanappa Shylaja; Dayananda S; Dakshayini M; Gangasagara Suresh; Prabhakaran Venkatesh (Indian Journal of Ophthalmology, 2010)
The occurrence of acquired conjunctival inclusion cysts following various ophthalmic surgeries such as strabismus surgery, scleral buckling, pars plana vitrectomy, ptosis surgery and phacoemulsification has been reported. We report two cases of conjunctival inclusion cysts following manual Small Incision Cataract Surgery (SICS) in two male patients aged 65 and 67 years. The cysts originated from the scleral tunnel used for manual SICS. Both were treated by excision and confirmed histopathologically. No recurrence was noted at three months follow-up. To our knowledge, conjunctival inclusion cysts following SICS have not been reported previously. Careful reflection of conjunctiva during tunnel construction and posterior chamber intraocular lens implantation may prevent their occurrence.